Superficial Mycoses Associated with Diaper Dermatitis - Bonifaz, Alexandro (Mycopathologia, 2016)
Diapers create particular conditions of moisture and friction, and with urine and feces come increased pH and irritating enzymes (lipases and proteases). Fungi can take advantage of all these factors. Candida yeasts, especially C. albicans, are responsible for the most frequent secondary infections and are isolated in more than 80 % of cases. Correct diagnosis is important for ensuring the correct prescription of topical antimycotics. Nystatin, imidazoles and ciclopirox are effective. It is important to realize there are resistant strains. Dermatophytes can infect the diaper area, with the most common agent being Epidermophyton floccosum. The clinical characteristics of dermatophytosis are different from those of candidiasis, and it can be diagnosed and treated simply. Malassezia yeasts can aggravate conditions affecting the diaper area, such as seborrheic dermatitis, atopic dermatitis, and inverse psoriasis. Additional treatment is recommended in this case, because they usually involve complement activation and increased specific IgE levels. Erythrasma is a pseudomycosis that is indistinguishable from candidiasis and may also occur in large skin folds. It is treated with topical antibacterial products and some antimycotics.